Analisis Struktural dan Pendekatan Moral dalam Cerpen “Siapakah Keluarga dari Tubuh yang Kacau Itu?” Karya Radja Sinaga - Yelvita Pratama Candra; Abdurahman Abdurahman (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2026)
This study aims to analyze the short story “Siapakah Keluarga dari Tubuh yang Kacau Itu?” by Radja Sinaga using structural and moral approaches in order to obtain a comprehensive understanding of its content and meaning. The structural approach is employed to examine intrinsic elements, including theme, characters and characterization, plot, setting, point of view, language style, and message. Meanwhile, the moral approach is used to reveal the ethical values and life lessons contained in the short story. This study applies a descriptive qualitative method, with data collected through library research by means of intensive reading and systematic note-taking of the text. The results show that the short story demonstrates a strong structural unity, with the main theme focusing on human suffering caused by war and the loss of family. In addition, several moral values are identified, such as humanity, familial love, criticism of violence, loss of identity, and resilience in facing suffering. The use of the second-person point of view also strengthens the reader’s emotional engagement with the story. Therefore, the combination of structural and moral approaches provides a deeper understanding of the meaning of the short story and its relevance to real-life contexts. This study is expected to enrich literary studies and enhance readers’ appreciation of literary works.